Handleyomys intectus (Rodentia: Cricetidae). (13th August 2019) - Vargas, Laura M; Ramírez-Chaves, Héctor E; Velazco, Paúl M
Abstract: Handleyomys intectus (Thomas, 1921) is a rodent commonly called the Colombian rice rat or white-footed Handley's mouse. It is a dull brownish-gray to blackish small mouse with frosted ventral pelage and with dark gray and pure-white (or indistinctly pigmented) hairs over the dorsum of hindfeet. H. intectus is endemic to the Central Andes of Colombia and it is known from several localities between 1, 500 and 2, 800 m. It may be a common species along its distribution. Globally, it is considered "Least Concern" by the International Union for Conservation of Nature and Natural Resources.